Sexual intimacies in displaced environment - Collado, Zaldy C. (Animo Repository, 2020)
© 2020, © 2020 College of Sexual and Relationship Therapists. This qualitative study examined the sexual intimacies of marital partners in displaced environment. Empirical material was obtained through semi-structured, face-to-face interviews with 12 Internally Displaced Persons (IDP) husbands. Due to conflict, they were forced to leave their communities of origin in Marawi City, in the Philippines, consequently displacing them into crowded evacuation sites and home-based accommodations. The participants were selected through purposive homogenous sampling. Transcripts were reviewed and subjected to thematic analysis. Results revealed less opportunities for sexual activities owing to unconducive environment—tight physical set-up, and presence of a number of people in the immediate surroundings. In addition, fear of pregnancy and prioritizing family’s basic needs (e.g. food) significantly discouraged couples to indulge in sexual intimacies. Despite the situation, participants were able to employ strategies to fulfill their sexual needs such as “visiting”, “timing”, and “paying” strategies. Unfulfilled sexual needs were reported to cause minor tensions between couples. However, mutual understanding and marital communication appeared to effectively mitigate the impacts. The practical implications and future research are discussed.